Structural conformation of Bacillus stearothermophilus F1 protease and effect of modification on its thermostability - Ibrahim, Noor Azlina; Rahman, Raja Noor Zaliha R. Abd.; Rahman, Mohd. Basyaruddin Abd.; Basri, Mahiran; Salleh, Abu Bakar (Penerbit Universiti Sains Malaysia, 2004)
The extracellular F1 serine protease, produced by a thermophilic Bacillus stearothermophilus F1, has been isolated and characterized as one of a serine protease. F1 protease was stable in the pH range of 8.0 to 10.0, with an optimum activity at pH 9.0. The enzyme was stable for 24h at 70°C (Rahman et al., 1994).